2015
DOI: 10.1080/03079457.2015.1083094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold stress on the pathogenesis of necrotic enteritis in broiler chicks

Abstract: Cold stress is a physical environmental stressor with significant effect on the poultry industry. The aim of the present study was to investigate the effect of cold stress as a predisposing factor for necrotic enteritis in broiler chicks. The experimental challenge model included an oral inoculation with 10-fold dose of attenuated anticoccidial vaccine and multiple oral inoculations with a specific strain of Clostridium perfringens. Birds were either challenged or not as described above, and either exposed or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
2
28
1
3
Order By: Relevance
“…For example, chickens on organic farms not administered antimicrobials exhibit higher colonization rates by C. perfringens [ 8 , 42 ]. Our results are in agreement with other studies in poultry that have demonstrated that potential stressors experienced during production, such as heat and cold temperature exposures and high stocking densities, can be associated with increased densities of C. perfringens [ 43 , 44 , 45 ]. It is unclear from the results of the current study, as well as previous reports, whether increased C. perfringens densities may have been a contributor to altered bacterial diversity observed in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, chickens on organic farms not administered antimicrobials exhibit higher colonization rates by C. perfringens [ 8 , 42 ]. Our results are in agreement with other studies in poultry that have demonstrated that potential stressors experienced during production, such as heat and cold temperature exposures and high stocking densities, can be associated with increased densities of C. perfringens [ 43 , 44 , 45 ]. It is unclear from the results of the current study, as well as previous reports, whether increased C. perfringens densities may have been a contributor to altered bacterial diversity observed in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear from the results of the current study, as well as previous reports, whether increased C. perfringens densities may have been a contributor to altered bacterial diversity observed in the current study. Previous reports linking stress with increased C. perfringens densities did not examine the intestinal microbiota [ 43 , 44 , 45 ]. The altered structure of bacterial communities that we observed, which coincided with increased C. perfringens, are not mutually exclusive factors as C. perfringens only increased in birds receiving CORT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cold stress was found to affect the thigh muscle of broilers more severely than the breast muscle, and it significantly reduced the feed intake and body weights of broilers but increased their feed conversion ratios [26,27]. As outdoor rearing systems gain more popularity, preventing cold stress will become increasingly costly to the poultry industry, and such costs often fluctuate depending on fuel prices, season, and existing heating systems [28].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature falling in point 1 to 4 within 25 min after starting the evaporative cooling system was 11.8°C, 8.7°C, 9.4°C and 9.9°C, respectively. A dramatic decreasing of environment temperature in short term might be a stress for poultry, which has potential to cause negative effects for poultry health [15], like increasing the pathogenesis of necrotic enteritis [16]. It could be concluded that the abrupt temperature drop caused by traditional regulation mode of evaporative cooling system might be a serious problem in summer.…”
Section: Improvement Of the Multistage Regulation Methodsmentioning
confidence: 99%